Legal Analysis of the Exclusion of PT Danantara's Losses From State Financial Losses In Investment - Ruslina, Elli; Kartiko, Dimas Yureza (Journal of Law, Politic and Humanities, 2025)
Investment management by state-owned enterprises (BUMN) or entities related to state finances often raises legal issues, particularly when losses occur that impact state finances. PT Daya Anagata Nusantara (PT. DANANTARA) is an entity that has been in the spotlight due to allegations of state losses arising from its investment management activities and the status of those losses. However, the emergence of exceptions to these losses from the category of state financial losses has given rise to legal debate that requires in-depth analysis. The method used in this research is a descriptive analytical method by solving research problems on the object of study, namely regarding Legal Analysis of PT Danantara's Exclusion from State Finance in Investment. The results of the study concluded that the exclusion of PT Daya Anagata Nusantara's (PT Danantara) losses from the category of state losses is based on a strong legal basis, especially referring to the legal status of PT Danantara as a limited liability company subject to private law and the principle of separate legal entity as regulated in the Law on Limited Liability Companies. The legal consequences of the exclusion of Daya Anagata Nusantara's (PT. DANANTARA) losses from the category of state finances due to investment management from the perspective of statutory regulations have a strategic position as a state investment management body that is directly responsible to the President. As a limited liability company, PT Danantara is legally separated from state finances as regulated in the State Finance Law No. 17 of 2003, so that the losses it experiences are not automatically categorized as state losses.